Blood and iron : stories and storytelling in Homer's Odyssey - Olson, S. Douglas. (Mnemosyne, Supplements, 1995)
Blood and Iron is an exploration of the role of gossip, rumor and storytelling in the society depicted in the Odyssey and in the real world in which the poem was performed. It includes extensive analysis of Homeric narrative technique, with particular attention to the way the singer creates tension in a largely traditional tale. Individual chapters treat discrete, generally very traditional literary and historical problems, including the significance of the term kleos , the presentation of Telemachos, the internal chronology of the poem, the nature of Homeric kingship, and the role of violence in the ancient Greek family. The book will be of importance for anyone interested in the literary content or storytelling technique of Homeric epic, as well for historians of the late Dark Ages.